Pengaruh Kualitas Produk Glad2Glow terhadap Kepercayaan Konsumen dan Keputusan Pembelian Skincare Glad2glow pada Social Commerce Tiktok Shop di Kabupaten Tasikmalaya - Ratna Dewi; Ardhiansyah Ardhiansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to examine the influence of Glad2Glow product quality on consumer trust and purchasing decisions for Glad2Glow skincare products through the online platform TikTok Shop in Tasikmalaya Regency. The research employed a quantitative approach using a survey method involving 60 respondents who had previously purchased Glad2Glow skincare products. Data were collected through a questionnaire based on a Likert scale ranging from 1 to 5. The collected data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique with the SmartPLS application. The results indicate that product quality is the strongest factor influencing consumer trust, with a path coefficient of 0.737 (T = 9.938; P = 0.000). Product quality also has a significant effect on purchasing decisions, with a coefficient of 0.505 (T = 6.129; P = 0.000). These findings demonstrate that better product quality increases consumer confidence in the product and encourages stronger purchasing decisions. The study highlights the importance of maintaining product quality as a strategic factor in building consumer trust and improving purchasing behavior in a social commerce environment. Therefore, businesses operating through digital platforms such as TikTok Shop should prioritize product quality to strengthen customer relationships and enhance market competitiveness.